Identifying quality indicators for home care services: a modified Delphi and Analytic Hierarchy Process study - Qiu-Lan Zheng; Ling-Na Kong; Ping Hu; Dun-Xiu Liu (BMC, 2024)
Abstract Background As the recipients of home care services, patients have the most direct and profound experience of service quality. There is limited knowledge as to quality indicators for home care services from patients' perspective. This study aimed to identify quality indicators for home care services based on the Service Quality model and determine the weights of these indicators. Methods A two-round Delphi survey and Analytic Hierarchy Process consultation were conducted to gather opinions from national experts on quality indicators for home care services developed on the basis of the Service Quality model. Consensus was defined as at least 80% agreement on the importance (important and very important) of indicators among experts. The Analytic Hierarchy Process was used to calculate the weight coefficients of the identified indicators. Results The response rate was 95.0% and 97.4% in the first and second round, respectively. After two rounds, five first-level (tangibility, reliability, responsiveness, assurance and empathy) and 23 second-level indicators were identified. The Kendall's W values were 0.54 and 0.40 for the first-level and second-level indicators (p < 0.001). The weight coefficients for the first-level and second-level indicators were 0.110-0.298 and 0.019-0.088, respectively. Conclusion Quality indicators for home care services were identified based on the Service Quality model. These indicators can be used to evaluate the service quality of home care from patients' perspective and facilitate to determine work priorities and improve the quality of home care.